2007
DOI: 10.1017/s0025315407054227
|View full text |Cite
|
Sign up to set email alerts
|

Embryology and early ontogeny of an anemonefish Amphiprion ocellaris

Abstract: The present study describes the embryonic development and early ontogeny of Amphiprion ocellaris from fertilization to post hatching. Anemonefish spontaneously spawned at 27-28°C. The newly laid eggs were orange in colour and elliptical in shape (1.8×0.8 mm). Melanin appeared as a black mass situated at the vegetal pole in mature eggs. This is rarely seen in eggs of other fish species. We documented developmental times at 27-28°C to egg activation (0.5 h), cleavage (4 h), blastula (11.5 h), gastrula (20 h), ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 31 publications
(41 reference statements)
2
19
0
8
Order By: Relevance
“…The characteristic ontogenesis of the eye, that develops a strong metallic silver color throughout time, is useful for following embryo development and predicting hatching. Liew et al (2006) and Yasir & Qin (2007) investigated the embryo development process in A. ocellaris at 27-28 °C and found consistent differences in the development rate. Generally, incubation lasts for 6 to 8 days at water temperature of 28 °C for most clownfish species (Olivotto et al, 2008a,b;Dhaneesh et al, 2009.…”
Section: Embryo Developmentmentioning
confidence: 86%
See 2 more Smart Citations
“…The characteristic ontogenesis of the eye, that develops a strong metallic silver color throughout time, is useful for following embryo development and predicting hatching. Liew et al (2006) and Yasir & Qin (2007) investigated the embryo development process in A. ocellaris at 27-28 °C and found consistent differences in the development rate. Generally, incubation lasts for 6 to 8 days at water temperature of 28 °C for most clownfish species (Olivotto et al, 2008a,b;Dhaneesh et al, 2009.…”
Section: Embryo Developmentmentioning
confidence: 86%
“…Liew et al (2006) and Yasir & Qin (2007) investigated the embryo development process in A. ocellaris at 27-28 °C and found consistent differences in the development rate. Yasir and Qin (2007) found that the development rate is first slower than in Liew et al (2006) but then drastically increased. In Yasir and Qin (2007) the first cleavage appeared at 4 hpf, blastula at 11.5 hpf, gastrula at 20 hpf, neurula at 24.5 hpf, first somites at 28.5 hpf and hatching occurred 152 hpf.…”
Section: Embryo Developmentmentioning
confidence: 86%
See 1 more Smart Citation
“…Berbeda dengan ikan hias clown hitam (Amphiprion percula) yang memiliki bentuk lonjong dengan kisaran ukuran yang relatif lebih besar dari telur ikan letter six dengan ukuran 2,21 x 0,89 mm (Kusumawati & Setiawati, 2010). Sedangkan pada ikan clown biasa (Amphiprion ocellaris) memiliki bentuk lonjong dengan ukuran 1,8 x 0,8 mm (Yasir & Qin, 2007), sementara itu, pada jenis ikan clown lainnya yaitu Amphiprion akallopisos memiliki kisaran ukuran 2,21 x 1 mm (Dhaneesh et al, 2011). Pada ikan hias lainnya yaitu dari jenis ikan goby (Priolepis nocturna) memiliki bentuk oval dengan ukuran lebih besar dari ukuran telur ikan letter six yaitu 0,82 x 0,51 mm (Wittenrich et al, 2007).…”
Section: Hasil Dan Bahasan Pemijahan Induk Dan Perkembangan Embriounclassified
“…Durasi perkembangan embrio ikan letter six terjadi dalam waktu 22 jam 24 menit (Tabel 1). Dalam kondisi suhu air yang sama yaitu berkisar 27°C-28°C, perkembangan embrio ikan letter six relatif lebih cepat jika dibandingkan dengan ikan hias laut dari jenis Amphiprion di mana pada ikan A. ocellaris dan A. kallopisos memerlukan waktu yang sangat lama yaitu 152 jam (Yasir & Qin, 2007;Dhaneesh et al, 2011). Sedangkan pada ikan jenis goby (Priolepis nocturna) memerlukan waktu 96 jam untuk larva bisa menetas (Wittenrich et al, 2007).…”
Section: Hasil Dan Bahasan Pemijahan Induk Dan Perkembangan Embriounclassified